Pain reduction induced by tapentadol in patients with musculoskeletal chronic pain fosters better sleep quality - Renato Vellucci; Gianluca De Rosa; Emanuele Piraccini (BioExcel Publishing Ltd, 2021)
Background: Poor sleep may predict the increase and intensification of pain over time with increased insomnia symptoms being both a predictor and an indicator of worse pain outcomes and physical functioning status over time. However, the impact of different analgesic therapies on quality of life, functional recovery and sleep has been poorly assessed to date, whereas these evaluations may greatly help clinicians in the selection of treatment when dealing with patients with chronic pain (CP). Methods: To explore whether tapentadol-induced pain relief may drive improved sleep quality, we carried out a pooled analysis of real-world data collected from 487 patients with CP (mean age, 68.3 years; 57.7% women) suffering from a wide range of chronic musculoskeletal pain conditions and treated with tapentadol. Results: Following tapentadol treatment, patients experienced an 80% reduction in the frequency of very disturbed sleep as well as a 50% reduction in the predominant sleep complaint reported by patients with CP - that is, nocturnal awakenings. A significantly greater proportion of patients reported good/restful sleep at the end of the study period compared to baseline (72.4% versus 25.3%; p<0.01). This benefit was observed regardless of the clinical setting, treatment duration, posology or patient age and was associated with a higher proportion of patients reporting an improved global health status and good tolerability. Conclusion: The reduction in pain intensity provided by tapentadol fosters sleep quality and favours a better quality of life. Therefore, our findings provide the rationale for addressing sleep quality as a relevant outcome, complementary to pain relief in CP management.